Designing a Secure System using Encrypted Radio Waves - Jabr, Noorulhda Mohamed Shaewit; Yasser, Batool Mahdi Anad; Shandoo, Abdullah Naeem Habeeb; Dawood, Atheer Haitham Hasson (American Journal of Botany and Bioengineering, 2025)
Designing a secure system based on encrypted radio waves aims to safeguard data transmission through advanced encryption techniques that prevent signal interception or manipulation during transit. This system incorporates various technologies, such as dynamic encryption protocols, frequency control, and identity verification systems, to ensure that transmitted and received signals are fully protected. This research focuses on integrating radio encryption with intrusion detection systems and ensuring vulnerability analysis to develop comprehensive solutions that confidentiality, integrity, and availability in all operations relying on radio waves.